Proposal of Social Return on Investment Assessment to Enhance Community Empowerment Grant Management in Malaysia - Wong, Mohd Muhaimin Ridwan; Zahari, Haliza Mohd; Ahmad, Noor Diyana Fazan; Shukor, Nurul Naqirah; Abas, Fuad; Husin, Wan Norhasniah Wan (P3M Politeknik Negeri Jember, 2025)
The Malaysian government, through its various ministries and agencies, strive to empower communities via various policies and funding programs. One significant initiative during the post-COVID-19 recovery period is the Malaysian Incentive Community Empowerment program. This program provided funds to over 2,000 non-governmental organisations to conduct community programs focused on four aspects: security, well-being, leadership, and cooperation with public agencies. While the number of communities benefiting from the funding program was encouraging, interviews with the agency responsible for administering the funding and assessment of program reports revealed a lack of adequate and systematic evaluation for program outputs and the returns on the investment made by the government. Evaluating social impacts particularly those resulting from the use of public funding is crucial to ensure accountability, transparency, resource optimisation, social equity as well as for informed decision-making for future initiatives and policies. Therefore, this paper proposes the application of the Social Return on Investment approach by funding organisations and government agencies to measure and validate the impacts of publicly funded community programs. Additionally, this paper explores the reality of integrating this elaborate impact evaluation methodology in the broader administrative framework of the funding program, with particular attention on the opportunities and challenges presented by its implementation by local agencies.